Fault Tolerant Routing in Wireless Cellular Networks: An Approach for maximizing Call Acceptance and reducing Delay - Thakurta, Parag Guha; Sett, Sujoy; Choudhury, Spandan; Bhattacharya, Swapan; Bandyopadhyay, Shubhansu (INFOCOMP Journal of Computer Science, 2016)
In this paper, a fault tolerant routing scheme in wireless cellular networks is proposed for improving call acceptance and simultaneously reducing delay in spite of existence of Base Station fault. The local routing tables on the neighbours are created to identify the preference of any neighbouring base station for forwarding data. Using an Ant Colony Optimization (ACO) based approach, faulty regions in the network are detected and call requests are efficiently routed around such regions thus avoiding congestion. It determines the optimal routes in network with reduced delay. The experimental results confirm the theoretical findings and its effectiveness over existing approaches.